The best alternative? The use of alternative media in the occupy movement - O'Connell, John T., author; Switzer, Jamie, advisor; Kodrich, Kris, committee member; Mahoney, S. Pat, committee member (Colorado State University. Libraries, 2013)
This research study explores the use of alternative media among the Occupy social movement. A combination of factors, including emerging media technology and an antagonistic relationship with mainstream media has led many social movement actors to use alternative media to mobilize participation. The study looks into the participants' perspectives concerning mobilization through alternative media. Qualitative interviews with participants of Occupy Denver revealed insight into methods of mobilization, users' relationships with mainstream media sources, and vulnerabilities of alternative media use. The findings revealed that mobilization has been observed to occur successfully using open, interactive forms of online alternative media. Despite several risks identified with alternative media use, participants explained that Occupy Denver continues to prefer mobilizing through alternative media due to opportunities for horizontal structure, control, and independence from the mainstream media.